2015
DOI: 10.1016/j.ijppaw.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The African buffalo parasite Theileria. sp. (buffalo) can infect and immortalize cattle leukocytes and encodes divergent orthologues of Theileria parva antigen genes

Abstract: African Cape buffalo (Syncerus caffer) is the wildlife reservoir of multiple species within the apicomplexan protozoan genus Theileria, including Theileria parva which causes East coast fever in cattle. A parasite, which has not yet been formally named, known as Theileria sp. (buffalo) has been recognized as a potentially distinct species based on rDNA sequence, since 1993. We demonstrate using reverse line blot (RLB) and sequencing of 18S rDNA genes, that in an area where buffalo and cattle co-graze and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 45 publications
2
54
1
Order By: Relevance
“…sp. (buffalo) (Mans et al, : nodal support NJ = 65%; Mans et al, : NJ bootstrap value of 64); however, analysis using alternative markers has differentiated these as unique taxa (Bishop et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…sp. (buffalo) (Mans et al, : nodal support NJ = 65%; Mans et al, : NJ bootstrap value of 64); however, analysis using alternative markers has differentiated these as unique taxa (Bishop et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the majority of the cattle exhibited parasites with 1–2 MS7 alleles each. This possibly reflects a phenomenon that only a limited subset of T. parva genotypes can be transmitted by ticks to cattle, although the diversity of T. parva circulating between vector ticks and wildlife reservoirs is highly diverse (Allsopp et al, ; Bishop et al, ; Conrad et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The African cape buffalo are important wildlife reservoirs of T. parva and are typically infected with parasite populations exhibiting higher antigenic diversity than T. parva that can be transmitted between cattle by ticks (Obara et al., ; Pelle et al., ). In addition, it has recently been demonstrated that cattle immunized by (ITM) using the Muguga cocktail are susceptible to challenge with buffalo‐derived parasites (Bishop et al., ; Sitt et al., ). Genome sequencing of schizonts purified from cell lines (Hayashida et al., ), a comprehensive study of variation within the genes encoding the Tp antigens (Pelle et al., ) and VNTR analyses (Oura, Tait, Asiimwe, Lubega, & Weir, ) have all confirmed that the cape buffalo harbours a much greater diversity of T. parva genotypes relative to the strains transmissible between cattle by ticks.…”
Section: Discussionmentioning
confidence: 99%